(untitled) (Research, Society and Development, 2022)
Objective to discover the strategies used by nursing professionals to promote patient safety and prevent the occurrence of Adverse Events (AEs) in Intensive Care Units (ICU). It is an integrative review of the literature, where the research includes the original articles, which will respond to the objectives of the study. Data from the Biblioteca Virtual em Saúde (VHL), Medical Literature Analysis and Retrieval System online (Medline), Nursing Data Bank (BDENF) and SciVerse Scopus were used. The results presented are divided into three categories for discussion: common EAs in ICUs; Nursing Assistance for the prevention of two EAs and permanent education for the prevention of EAs. A predominance of studies published in the last decade is identified, with emphasis on Brazilian publications. The strategies used by nursing professionals to promote patient safety and prevent AE’s in the ICU were found and among them, stand out, in general, implementation of protocols, training of the team, use of technologies and correct notification of incidents.